2018
DOI: 10.11613/bm.2019.011003
|View full text |Cite
|
Sign up to set email alerts
|

A paradigmatic case of haemolysis and pseudohyperkalemia in blood gas analysis

Abstract: A 51-year old male patient was admitted to the hospital with acute dyspnea and history of chronic asthma. Venous blood was drawn into a 3.0 mL heparinized syringe and delivered to the laboratory for blood gas analysis (GEM Premier 4000, Instrumentation Laboratory), which revealed high potassium value (5.2 mmol/L; reference range on whole blood, 3.5-4.5 mmol/L). This result was unexpected, so that a second venous blood sample was immediately drawn by direct venipuncture into a 3.5 mL lithium-heparin blood tube,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Familial pseudohyperkalaemia was also considered in this case, since this can also result in spurious hyperkalaemia without haemolysis (18). This can be caused by a mutation in the ABCB6 transporter (formerly called "leaky cell membrane syndrome") and by several red blood cell membrane defects such as hereditary stomato-, xero-or spherocytosis (18,19). We did, however, not find any increase after storage for 2 hours at room temperature, excluding familial pseudohyperkalaemia as cause of the spurious hyperkalaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Familial pseudohyperkalaemia was also considered in this case, since this can also result in spurious hyperkalaemia without haemolysis (18). This can be caused by a mutation in the ABCB6 transporter (formerly called "leaky cell membrane syndrome") and by several red blood cell membrane defects such as hereditary stomato-, xero-or spherocytosis (18,19). We did, however, not find any increase after storage for 2 hours at room temperature, excluding familial pseudohyperkalaemia as cause of the spurious hyperkalaemia.…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of this anesthesiologist, it is often difficult to load a blood specimen into the POC testing cartridge without the formation of bubbles, which may alter test results for parameters such as blood gasses, and POC devices cannot detect sample quality interferents like hemolysis, leading to uncertainty when abnormally high or low results are obtained. [10][11][12] Although central labs are known to be more analytically reliable, this clinician has observed that when sending samples to the central lab from the operating room, pre-analytical error rates can reach up to 40%, likely due to transportation issues or mislabeling of the specimen itself.…”
Section: Perspectives On Blood-based Point Of Care Diagnostics Anesthmentioning
confidence: 99%